1984
DOI: 10.1136/hrt.51.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed noradrenergic blood pressure control in normotensive members of hypertensive families.

Abstract: The possible influence of a family history of hypertension on some variables of adrenergic blood pressure regulation was assessed. Blood pressure, heart rate, plasma renin activity, adrenaline and noradrenaline concentrations, and plasma or urinary electrolyte estimations did not differ significantly between two groups of normotensive subjects matched for age and sex with and without a family history of hypertension. Compared with subjects without a family history, however, an appreciably decreased pressor dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…We could not reconfirm the observation by Bianchetti et al 31 that a family history of hypertension was related to slope. We relied on unverified self-report of family history; thus, these data are subject to question.…”
Section: Discussioncontrasting
confidence: 99%
“…We could not reconfirm the observation by Bianchetti et al 31 that a family history of hypertension was related to slope. We relied on unverified self-report of family history; thus, these data are subject to question.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that a common familial disturbance which could possibly predispose to the development of essential hyper tension, was an imbalance between the cardiovascular noradrenaline responsiveness and the circulating noradrenaline [20]. The increased response to norepinephrine in the normotensive siblings of hypertensive parents was due to a reduced threshold to norepinephrine [21].…”
Section: Discussionmentioning
confidence: 99%
“…l6 Subjects with a family history of hypertension have higher catecholamine levels during stress" and show enhanced pressor response to exogenous catecholamines. 17 Bianchetti et al 18 noted lower mean levels of plasma NE in normotensive subjects with a history of hypertension than in those without such a history, though these differences did not reach statistical significance. Beilin et al" found higher levels of E but not NE in high normal compared with low normal blood pressure groups, although no account was taken of a family history of hypertension.…”
Section: Figure 3 Effect Of Alcohol (*) and Placebo (O) On Plasma Nomentioning
confidence: 96%